21. RAPE VICTIMS TO MARRY THEIR PERPETRATORS: REPRESENTATIONS OF MUSLIM LEADER AND OTHER PARTICIPANTS - Shamsi, Syuhaidah; Rashid Ali, Farrah Diebaa (Journal of Islamic, Social, Economics and Development, 2024)
The way journalists portray social actors in a discourse is one approach to observing the power the media wields in influencing public opinion. Speakers and writers can choose from a wide range of word choices to depict social actors in a particular discourse. These word choices have the power to shape how society views and interprets them, which can lead to the social construction of reality. A favourable portrayal of social actors would lead to a favourable perception within society and vice versa. This study examines how local and international news outlets represented a Malaysian Member of Parliament- a former Shariah court judge, the rape victims, the rapist and underage marriage in 35 headlines on the MP’s suggestion to legalise underage marriage, rape victims marrying their perpetrators included. The analysis was guided by van Leeuwen’s Social Actor Representation framework and Fairclough’s Critical Discourse Analysis (CDA) framework. The findings show that the Member of Parliament (MP) is represented through functionalisation, objectivation and formalisation. He was portrayed as someone who upholds the male-dominated patriarchal tradition. The victims and the perpetrators were assigned with the relational role of the rapist and their victims. The victims were seen as objects that negatively benefited from the process. Hence, they were advised to marry the perpetrator to have a better future. Although his suggestion was not in any way against Islamic teaching, his view was represented as an outrage in international headlines. The representations constructed in the headlines are consistent with numerous discourses that portray male social actors as more powerful and superior than their female counterparts.